2018
DOI: 10.18203/2349-2902.isj20182212
|View full text |Cite
|
Sign up to set email alerts
|

Validity of RIPASA scoring system as a diagnostic tool of acute appendicitis in comparison with Alvarado scoring system in the Arab population

Abstract: Background: RIPASA scoring has been developed to replace the disappointingly low accuracy Alvarado score in Asian population for diagnosis of acute appendicitis. Objective of present study was to compare the RIPASA and Alvarado score in Arab population and determine their accuracy when applied to our patients in Egypt and Kingdom of Saudi Arabia (KSA).Methods: By applying the RIPASA and Alvarado scores to 100 patients from KSA, 100 patients from Egypt who presented to emergency with right iliac fossa pain. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Nevertheless, this was lower than the 97.4% reported by Subramani et al [26] , and it is thought that this is because there were a lot truer negative instances recorded in their study compared to the sample size. Numerous researches [27] had shown that the RIPASA score's accuracy fell between 90.5% and 97.5%, which was comparable to the RIPASA's 94.8% claimed diagnostic accuracy in the current study. Although the current results were significantly higher than those of Pasumarthi et al [28] and Chae et al [23], this could be because many patients with urological symptoms were included in the study, which resulted in a significant number of false positive instances.…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, this was lower than the 97.4% reported by Subramani et al [26] , and it is thought that this is because there were a lot truer negative instances recorded in their study compared to the sample size. Numerous researches [27] had shown that the RIPASA score's accuracy fell between 90.5% and 97.5%, which was comparable to the RIPASA's 94.8% claimed diagnostic accuracy in the current study. Although the current results were significantly higher than those of Pasumarthi et al [28] and Chae et al [23], this could be because many patients with urological symptoms were included in the study, which resulted in a significant number of false positive instances.…”
Section: Discussionsupporting
confidence: 73%
“…Studies from Jordan, Kuwait, Iran, and Turkey as well as a multicenter, cross-border study between Saudi Arabia and Egypt corroborated the results of the original study in the Middle Eastern population as well [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 60%
“…Another investigation conducted in India demonstrated that the MASS had an SN of 64.44% and an SP of 58.82%, whereas the RIPASA score had an SN of 87.78% and an SP of 76.47% [22]. Research conducted in Jordan [23], Kuwait [21], Iran [24], and Turkey [5], together with a multicenter, cross-border study involving Saudi Arabia and Egypt [25], have confirmed the findings of the initial study in the Middle Eastern population. Malik et al conducted one of the initial assessments of the RIPASA scoring in a Western population in Ireland, following the observation of favorable outcomes in several Eastern investigations [26].…”
Section: Discussionmentioning
confidence: 99%